ARE WE TELLING THE DIABETIC PATIENTS ADEQUATELY ABOUT FOOT CARE? - Ali, Rashid; Farooq, Umer; Jalal-ud-din, Mir; Jadoon, Raheel Jahangir; Alam, Muhammad Adeel; Qureshi, Asfandyar; Shah, Syed Usman (Journal of Ayub Medical College Abbottabad, 2016)
Background: Diabetes mellitus affects more than 285 million people worldwide. The prevalence is expected to rise to 439 million by the year 2030. Diabetic foot ulcers precede 84% of non-traumatic amputations in diabetics. One lower limb is lost every 30 seconds around the world because of diabetic foot ulceration. Apart from being lengthy, the treatment of diabetic foot is also very expensive. There is very limited emphasis on foot care in diabetic patients. Even in developed countries patients feel that they do not have adequate knowledge about foot care. This study was conducted to find out how much information is imparted by doctors to diabetic patients about foot care. Methods: This cross-sectional study was conducted in admitted patients of the Department of Medicine, DHQ Hospital, Abbottabad from May 2014 to June 2015. 139 diabetic patients more than 25 years of age were included by non-probability consecutive sampling. Results: The mean age was 57.17 (±11.1) years. 35.3% of patients were male and 64.7% were female. The mean duration of diabetes in patients was 8.3 (±6) years. Only 36.7% of patients said that their doctor told them about foot care. Less than 40% of patients knew that they should daily inspect their feet, wash them with gentle warm water, and dry them afterwards. Only 25.2% of the participants knew how to manage corns or calluses on feet. 66.5% of patients knew that they should not walk bare foot. Overall, 63% of our patients had less than 50% knowledge of the 11 points regarding foot care that the investigators asked them. Conclusion: Diabetic foot problems are the one of the costliest, most disabling and disheartening complication of diabetes mellitus. Doctors are not properly telling diabetic patients about foot care. There is a deficiency of knowledge among the diabetic patients regarding foot care.